Dataset: Cyberlaw and Copyright in the 21st Century: A Comprehensive Analysis of Scholarly Works - Citra Sonia; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
This data article presents a collection of scholarly works related to Cyberlaw and Copyright in the field of law, obtained through the Lens.org website. The data were obtained by searching for scholarly works using keywords Cyberlaw or Cyber Law and Copyright and filtering them by document type (journal article), date range (2012-2022), and subject matter (law). The data were exported in CSV and BibTex formats and are available in the Zenodo repository. The analysis of the data using VOSViewer and Lens.org tools revealed the top institutions, fields of study, active authors, countries/regions, publishers, and journals. The results of this study provide a valuable resource for researchers and practitioners interested in the legal aspects of Cyberlaw and Copyright. Highlights: Valuable resource for Cyberlaw and Copyright research Comprehensive analysis of scholarly works from 2012-2022 Reveals top institutions, authors, and publishers in the field.